A educação sexual no contexto do ensino de biologia: um estudo sobre as concepções de professores/as do ensino médio em escolas de Uberaba - MG - Santos, Welson Barbosa (2010)
This research has investigated biology teachers comprehension regarding the possibilities and/or difficulties there are to face in the development of the sexual education. Based on the ideas of Parrot (1997, 1999 and 2000), Weeks (1999), Altman (2001, 2005 and 2007), Furlani (2008) and Cross (2008), amongst others, it s assumed that the exclusively anatomical-physiological boarding does not serve the needs or answer the questions of young adolescents and does not face the challenges presented for the sexual education of our time. On the other hand, inhaled in Freire (2006) it is defended the dialogued and critical boarding, that installs an open, free, aesthetic and ethic conversation between teachers and students in matters subject to sexuality. To achieve the point of view of biology teachers regarding the conditions that promote a critical boarding of sexual education focal groups techniques were used. Six biology secondary school teachers of Uberaba/MG, that had taught sexual education in its lessons took part of the focal group. The raised data showed that teachers attempt to develop the subject of sexual education upon the dialogue with the adolescent students, however, this practices shows out to be a great challenge, they try to overcome using their professional experience and the National Curricular Parameters, mainly. The biggest objections or difficulties teachers find when working sexual education are the restricted initial formation, limited to the domain of a specific area, the omission of families and the unpreparedness and disinformation of students.